Estudio preliminar morfológico y morfométrico de encéfalo del pez tiburoncito, Ariopsis seemanni, (Pisces: Ariidae) - Claudia Londoño; Hernán Hurtado Giraldo (Universitas Scientiarum)
Preliminary morphologic and morphometric study of the encephalon of the tiburoncito Ariopsis seemanni (Pisces: Ariidae)Objective. To describe morphologically and morphometrically the encephalon of Ariopsis seemanni. Materials and methods. We workedwith 10 juvenile specimens which were processed according to the ethical standards for handling fish. Measurements of the total andstandard length (cm) and weight (g) were taken for each individual. Specimens were fixed in 4% formaldehyde. The encephalon wasremoved, the different regions were identified and the measurement of the different lobes was done, indicating their location, morphology,length and area using lateral, dorsal and ventral digitalized images that were measured with the Scion Image program. We calculated meansand standard deviations, and obtained the percentage equivalence of each structure in relation to the entire encephalon. These data were thenrelated to the habits of the species. Results. We identified the olfactory bulbs, telencephalic hemispheres, optic lobes, cerebellum, amongothers. Of the cranial nerves, only the optic nerve was observed. The largest structure of the encephalon is the cerebellum (44 ± 1.2% and0.23 ± 0.03 cm2 area), followed by the telencephalic hemispheres (28 ± 0.57% and 0.13 ± 0.02 cm2 area). Conclusions. The encephalonmorphology of A. seemanni presented the general pattern of teleosts of the order Siluriformes, with the cerebellum as the largest structureof the encephalon. Based on the morphology and morphometry observed in the encephalon, we suggest that A. seemanni uses primarilyvision and taste to explore the environment.